PERBEDAAN GENERASI PADA ANGKATAN KERJA YANG MEMPENGARUHI PERILAKU ORGANISASI: SEBUAH TINJAUAN SISTEMATIS - AZHARI AFRIZAL RAMLI; ABDUL WAHAB HASYIM; SULFI ABDUL HAJI (STIE Indonesia Malang, 2023)
Generational difference are a hot issue today. This is due to changes in the workforce in recent years. The composition of the workforce is currently filled by three generations that is Baby Boomers Generation, Generation X, and Generation Y, in which the three generations have different characteristics and can be a challenge for organizations, so organizations need to manage these three generations to be profitable for organization. The method used in this paper is based on a systematic review based on a comprehensive database search to identify a complete list of literature on generational differences through journal articles, proceedings, theses, books and online news. This systematic review of studies specifically aims to examine empirical studies that investigate generational differences in the workforce that influence organizational behavior. Based on a systematic review, empirical evidence points to some significant intergenerational differences today at work in modern organizations.Keywords: Generational Differences, Baby Boomers Generation, Generation X, Generation Y, Organizational Behavior